Efecto citotóxico y genotóxico del extracto acuoso de Physalis peruviana L. (aguaymanto) sobre células meristemáticas de Allium cepa (cebolla) y linfocitos - Santa Cruz López, Cinthya Yanina (2019)
ABSTRACT The search for phytotherapeutic products used to treat multiple diseases represents an area of great interest. However, its correct use must be ensured with the lowest possible risk to health. Since, extracts of vegetables used for medicinal purposes that have mutagenic and carcinogenic activity are known. The present study evaluated the cytotoxic and genotoxic effect of the aqueous extract of Physalis peruviana L. (golden berry) at concentrations of 10, 20 and 30mg / ml on Allium cepa (onion) meristematic cells and at concentrations of 62.5, 100, 250 and 1000 ug/ml on human lymphocytes. 12 onion bulbs were used, subjected to extract concentrations of 10, 20 and 30mg/ml and a control group (3 repetitions each), then coloration, assembly and microscopic reading were made at 400 and 1000x, evidencing the decrease of the mitotic index and phase index in the concentrations evaluated, with respect to the control and, aberrations were observed as binucleated cells and chromosomal bridges. While, the lymphocytes were obtained from the peripheral blood of three donors aged between 24 and 30 years and exposed for thirty minutes to extract concentrations of 62.5,100, 250 and 1000 ug/ml, taking H2O2300 μM and PBS 1X as positive and negative controls respectively (3 repetitions each), observing the decrease in the viability of the lymphocytes, increase in the cell damage index, percentage of DNA, moment of the tail and the Olive moment. It was concluded that the aqueous extract of Physalis peruviana L. has a cytotoxic and genotoxic effect at concentrations of 10, 20 and 30 mg / ml on Allium cepa meristematic cells and at concentrations of 62.5, 100, 250 and 1000 ug / ml on lymphocytes. humans.